THE CONSUMER PROTECTION ACT AND THE INNKEEPER’S LIABILITY FOR THE PROPERTY OF THE GUEST - Mark Tait (Obiter, 2017)
Literally thousands of consumer agreements are concluded every day between innkeepers and their guests. For present purposes an innkeeper is understood to be a supplier of accommodation services and, in turn, implies the proprietor of an accommodation establishment, such as a hotel, lodge and bed and breakfast establishment. It is unfortunately not uncommon that property of some consumers of accommodation services are damaged or lost through theft or other causes whilst making use of these services. As an example may serve a media report where the Daily Dispatch reported on an incident stemming from an alleged theft by employees of the Kariega Game Reserve from guests at the Reserve. This perennial problem raises the issue as to the liability of the supplier for loss of or damage to the property of the consumer whilst the latter is making use of the accommodation services of the supplier. In the praetorian edict de nautius, cauponibus et stabulariis the common law provides a specific solution as to the liability of the supplier. The edict, which is a consequence of the contract for accommodation services between the supplier and the consumer of those services, imposes strict liability on the supplier for loss of, or damage to, the property of the consumer. This protection, however, is largely negated by the general practice of expressly excluding the liability imposed by the edict in the consumer agreement between the parties.The introduction of the Consumer Protection Act 68 of 2008 (CPA) saw a number of specific provisions impacting the relationship between consumer and supplier of accommodation services – such as provisions pertaining to equality (s 8 and 9); privacy (s 11 and 12); cancellation of advance reservations (s 17); and customer loyalty programmes (s 35), to name but a few.The CPA also has implications for the supplier of accommodation services when it comes to the supplier’s liability for the loss of, or damage to, the property of the consumer. This note focuses on two particular aspects. The first considers briefly the impact of the Act on clauses excluding the liability of the supplier for loss or damage to the consumer’s property. Provisions of the CPA regulating the use of clauses excluding liability may therefore have relevance for the praetorian edict, as the protection provided by the edict is excluded as a standard practice, as stated. The edict, because of the impact of the CPA, therefore may resume its relevance of earlier years.The second aspect pertains specifically to section 65(2) of the CPA. This provision imposes a duty on suppliers in general to account for the property of the consumer when such property is in possession of the supplier. As a matter of course guests bring property into the accommodation establishment of the innkeeper with which the consumer has contracted. If such property is lost or damaged (through no fault of the consumer) the question arises whether section 65(2) can find application. If it does, it can have significant consequences for both suppliers and consumers, but if not, then an understanding of the impact of the CPA on the use of clauses in a consumer contract excluding liability becomes even more important.